Design and characterization of metal coatings on high temperature polymers for harsh environment electronics board - Ong, Si Hui (Nanyang Technological University, 2021)
Commercially, polymers such as polyimide, epoxy and FR-4 are the most commonly used electronic packaging material. However, for high temperature applications such as in the aerospace and marine industries, these polymers are reaching their mechanical and thermal limits. Intensive research has been conducted on an alternative polymer, phthalonitrile (PN), for its thermal conductivity and thermal stability in high temperature applications.